Population-specific evolution of natural killer cell diversity - Norman, Paul (Henry Stewart Talks, 2011)
NK cell Diversity; KIR and HLA, Genetic variety of human immune systems, Natural killer (NK) cell functions, HLA and KIR polymorphism, Genetic association with infectious disease, Pregnancy syndromes, Maintenance of diversity in populations, KIR haplotypes, balancing selection, population bottlenecks, human population diversity, Natural selection and functional variation, cell-free assays, allelic variants with altered specificities, Extent of Diversity in Populations, HLA/KIR compound genotypes and immune identity, Distribution of viable KIR/HLA interactions, KIR/HLA in Ancient Humans, Virtual HLA/KIR genotype of Denisova and Neanderthal, Distribution of ancient human KIR/HLA alleles in modern humans